2021
DOI: 10.1200/edbk_320041
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care: Low Cost, High Value

Abstract: Supportive care aims to prevent and manage adverse effects of cancer and its treatment across the entire disease continuum. Research and clinical experience in dedicated centers have demonstrated that early appropriate supportive care interventions improve symptoms, quality of life, and overall survival in a cost-effective manner. The challenge is to assess symptoms and needs with validated tools regularly and, ideally, between clinic appointments; electronic patient-reported outcome measures and dedicated eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
(55 reference statements)
0
8
0
Order By: Relevance
“… 34 Additionally, for fatigue, addressing comorbid conditions and optimizing sleep and exercise are likely to be more effective than costly modafinil. 47 Payer noncoverage and high out-of-pocket costs of nonpharmacologic interventions (such as acupuncture or exercise regimens) for symptom control are partly responsible for their underutilization. 48 Our data demonstrate that even simple, seemingly innocuous drug prescriptions can cause significant economic consequences to patients.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Additionally, for fatigue, addressing comorbid conditions and optimizing sleep and exercise are likely to be more effective than costly modafinil. 47 Payer noncoverage and high out-of-pocket costs of nonpharmacologic interventions (such as acupuncture or exercise regimens) for symptom control are partly responsible for their underutilization. 48 Our data demonstrate that even simple, seemingly innocuous drug prescriptions can cause significant economic consequences to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise may be beneficial for patients with HL receiving BV, even though evidence that exercise rehabilitation strategies may be effective in patients with CIPN is limited to date and no definitive data to conclude that exercise interventions ameliorate established CIPN are available. With respect to the latter, this is in part due to small sample sizes, variable outcome measure selection, and little data on how exercise affects CIPN mechanistically [ 127 , 128 ]. Similarly, there is a growing body of literature to suggest that exercise could even prevent CIPN [ 129 ].…”
Section: Early Diagnosis and Management Of Bvinmentioning
confidence: 99%
“…In extreme cases, CRF can limit the ability of cancer survivors to reintegrate into normal life and return to work [ 6 ], and FOR can lead to despair, low morale, and even suicidal thoughts [ 7 ], creating a heavy burden. Clinical studies and experiences have shown that appropriate early mind–body interventions can improve cancer patients’ physical and mental symptoms, QOL, and overall survival rate [ 11 ]; enhance their self-management ability and confidence through lifestyle changes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, malnutrition is very common in cancer survivors [ 11 , 34 , 35 ]; 89% of cancer survivors believe that nutrition is extremely important in cancer care, and 57% indicate that more nutrition interventions are needed [ 35 ]. Appropriate nutritional assessment and early intervention can reduce the physical and mental stress caused by cancer [ 2 ], improve cancer survivors’ overall physical and mental health and QOL and reduce the risk of cancer progression [ 34 ].…”
Section: Introductionmentioning
confidence: 99%